Uso da regra ABC de Pareto para organização de um armazém em uma empresa de carroceria florestal - Oliveira, Matheus Giglio de (2022)
It is known that nowadays the competition between companies is increasing and the number of existing companies is also growing, demanding an agile and simplified production. The market for forestry bodies and bunks is no different, there is great demand in the market and to meet the requirements of this market, it is necessary that the production process of assembling components is structured and working in synchrony so that the production process flows and deliveries are carried out within the specified period. Faced with this situation, the challenge is to improve the production process, so that they can meet market requirements with shorter delivery times, maintaining production quality in a reduced time, making it more competitive compared to competitors in the sector. The incorrect positioning of components in the production environment results in excessive displacement of employees, delay in production and consequently in the delivery of orders to customers. In this way, this work proposes to organize the items in a warehouse as well as to propose its best location within the production process. Thus, this work aims to propose the creation of a warehouse to store the raw materials used throughout the production process. In order to meet this objective, the following steps were taken: survey of the materials used throughout the production process; verification of the distance traveled by employees to assemble each order; elaboration of the ABC curve considering the most used materials; and then a proposal for a warehouse was made, verifying the distance traveled by employees. The warehouse was proposed considering the ABC rule, this curve was built taking into account the most used materials throughout the production process. It was observed that among the proposed layouts, the one that best reduced the loading time of the parts used was the one with the entrance door located next to the two most used areas throughout the production process. Thus, a reduction of up to 16.5% was achieved in relation to the initial personal commuting time.